Additional information for Leptoglossus impictus (Stål 1859) (Hemiptera: Heteroptera: Coreidae: Coreinae: Anisoscelini) from Patagonia, Argentina - Diez, Fernando (2016)
The Patagonian subregion belongs to the Andean region, and is comprised of two provinces: Central Patagonia and Subandean Patagonia. It extends from central Mendoza, widening through Neuquén, Río Negro, Chubut, and Santa Cruz, to northern Tierra del Fuego, and reaches Chile (Morrone 2006). The knowledge of terrestrial Heteroptera in this region is poor and is limited to a few contributions (e.g. Berg 1979, Breddin 1898, Pennington 1920, Faúndez & Carvajal 2011, Faundez 2015).